Litter decomposition and nutrients dynamics in Nothofagus antarctica forests under silvopastoral use in Southern Patagonia. - Bahamonde, Héctor Alejandro; Peri, Pablo Luis; Alvarez, Roberto; Barneix, Atilio Jose; Moretto, Alicia Susana; Martínez Pastur, Guillermo José (Agroforestry Systems, 2012)
The role of environmental variables on litter decomposition and its nutrient release in Nothofagus antarctica forest in Patagonia is poorly understood. Moreover, in these forests under silvopastoral use there are few antecedents. Litter decomposition and nutrient release of grasses and tree leaves were evaluated under different crown cover and two site quality stands during 480 days. Organic matter decomposition varied with crown cover for both types of litter, achieving mean values of 23 and 34% for maximal and minimal crown cover, respectively. Total transmitted radiation was the main environmental factor explaining 61 and 49% of the variation of grass and tree leaves decay rates, respectively. N, P, and Ca were mineralized during first 60 days in decomposing tree leaves and then immobilized without differences between crown cover. The K was immobilized during the evaluated period. In decomposing grass leaves the results varied according to site quality and time. There was a tendency of nutrient mineralization at the first 120 days and then immobilization. The removal of trees for silvopastoral use of N. antarctica may increase litter decomposition by changing the microclimate, but nutrients release or immobilization was mainly affected for their concentration in decomposing material. EEA Santa Cruz Fil: Bahamonde, Héctor Alejandro. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Santa Cruz; Argentina. Fil: Bahamonde, Héctor Alejandro. Universidad Nacional de la Patagonia Austral; Argentina. Fil: Peri, Pablo Luis. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Santa Cruz; Argentina. Fil: Peri, Pablo Luis. Universidad Nacional de la Patagonia Austral; Argentina. Fil: Peri, Pablo Luis. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Fil: Alvarez, Roberto. Universidad de Buenos Aires. Facultad de Agronomía; Argentina. Fil: Barneix, Atilio Jose. Universidad de Buenos Aires. Facultad de ...